Recontextualization of the Concept of Kiai Leadership through a Distributed and Regenerative Approach for the Resilience of Islamic Boarding School Educational Institutions in the 21st Century - Nur Komariah; Jaenudin Jaenudin; Khairul Amin; Asmariani Asmariani; Irjus Indrawan (Journal La Edusci, 2025)
Centralized Kiai leadership, despite being the historical foundation of Islamic boarding schools (pesantren), faces significant challenges in addressing the complexities of the 21st century. This article discusses the recontextualization of Kiai leadership through the integration of distributed approaches and systematic regeneration to build institutional resilience. This research uses a Systematic Literature Review (SLR) following an adapted PRISMA framework. A literature search was conducted in indexed academic databases using a combination of keywords such as "Kiai leadership," "distributed pesantren leadership," and "pesantren leadership regeneration." Data analysis was conducted thematically on selected studies. The study produced a hypothetical model that transforms the Kiai's role from a single operational leader to a visionary-spiritual leader. Distributed leadership is realized through the empowerment of the asatidz council, senior santri, and professional staff in operational decision-making. This model is implemented in three integrative phases: foundation preparation, empowerment implementation, and ongoing maintenance. The synergy between distributed leadership and regeneration creates a sustainable leadership pipeline. Distribution of responsibilities serves as a laboratory for cadre development, while systematic regeneration ensures the availability and quality of potential successors. This integration allows Islamic boarding schools to maintain their traditional values (such as Uswah Hasanah and Zuhd) while increasing their adaptive capacity and pedagogical innovation, thus building strong organizational resilience in a disruptive era.